2015
DOI: 10.1038/srep09026
|View full text |Cite
|
Sign up to set email alerts
|

New Anti-angiogenic Leading Structure Discovered in the Fruit of Cimicifuga yunnanensis

Abstract: Cimyunnins A–C (1–3), characterized with an unusual fused cyclopentenone ring G, together with cimyunnin D (4), possessing a highly rearranged γ-lactone ring F, were characterized from the fruit of Cimicifuga yunnanensis. Their structures were elucidated by spectroscopic analysis, X-ray diffraction, and density functional theory calculations. In addition, cimyunnin A exhibited comparable anti-angiogenic activities to those of sunitinib, a clinically-used first-line angiogenesis inhibitor, in the in vitro and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Such changes of signaling molecules may be responsible for the inhibition of proliferation and migration of endothelial cells 43 44 . Previous studies showed that other cycloartane triterpenoids isolated from C. yunnanensis and Homonoia riparia exerted anti-angiogenic activities in HUVEC 6 45 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such changes of signaling molecules may be responsible for the inhibition of proliferation and migration of endothelial cells 43 44 . Previous studies showed that other cycloartane triterpenoids isolated from C. yunnanensis and Homonoia riparia exerted anti-angiogenic activities in HUVEC 6 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, being the allied species of C. racemosa (black cohosh), C. foetida (shengma) contains actein and many other bioactive cycloartane triterpenoids 6 28 . The new potential application of this herb for angiogenesis-dependent diseases warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cimyunnins A–D ( 560 - 563 ) and cimyunnin D ( 563 ), characterized a fused cyclopentenone ring G and a rearranged γ-lactone ring F, respectively, were identified from the fruit of Cimicifuga yunnanensis (Daocheng, Sichuan, China). Cimyunnin A ( 560 ) displayed a similar anti-angiogenic activity as sunitinib both in vitro and ex vivo (Nian et al, 2015 ). Macrophypenes A–E, five new diterpenoids, were isolated from leaves of Callicarpa macrophylla (Guangxi, China).…”
Section: Terrestrial Plantsmentioning
confidence: 99%
“…Black cohosh is a North American perennial plant that has been used for centuries by Native Americans. Evidence showed that it has been involved in multiple processes, including anti-inflammation, anti-rheumatism, pain killers, and anti-dysmenorrhoea [ 6 , 7 ]. In recent years it has become a common alternative in hormone replacement therapy for females to relieve menopausal symptoms.…”
Section: Introductionmentioning
confidence: 99%